Marketing Strategy of YouTube in the Czech Republic - Hurychová, Andrea; Král, Petr, 1979-; Tisovski, Marija; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The goals of the thesis are to present YouTube in the Czech Republic, to discuss its entire business model, analyze the main local competitors and mostly to suggest marketing strategy that will strengthen the position of YouTube as an online medium. The current trends in the internet society are introduced as well as the role of social media in order to understand how these factors are related to the position of YouTube in marketing. From general YouTube introduction the situation of this platform in the Czech market is analyzed. Based on this deep analysis, the key factors that should be taken into account in the Czech YouTube marketing strategy will be discussed.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses